Isolasi Dan Identifikasi Mikroba Penghasil Antibiotika Dari Sampel Lumpur Sungai Kampar Riau - Musyirna Rahmah Nst; Akmal Djamaan; Gustina ' (Universitas Riau, 2010)
Isolation of microbes that produce antibiotic found in the sludge of Kamparriver has been carrie out using crowded plate method. The sludge were inoculated inPDA and NA, and incubated for 24 hours. Microbes showing clear zone wereobserved, this indicated the microbes produce antibiotics. The microbes wereisolated and identified. The result showed there were three species Bacillus sp ofwhich potencial to produce antibiotic compund.Key words: microbe, isolation,antibiotic